Joan of Arc a history - Castor, Helen (Harper, an imprint of HarperCollins Publishers, 2015)
"The story of one of the most remarkable women of the medieval world, as you have never read it before. In Joan of Arc : a history, Helen Castor tells this gripping story afresh: forwards, not backwards. Instead of an icon, she gives us a living, breathing woman confronting the challenges of faith and doubt, a roaring girl who, in fighting the English, was also taking sides in a bloody civil war. We meet this extraordinary girl amid the tumultuous events of her extraordinary world where no one--not Joan herself, nor the people around her, princes, bishops, soldiers or peasants--knew what would happen next"--Provided by publisher.